Workplace bullying and harassment: new developments in international law - Cobb, Ellen Pinkos (New York, 2017)
"Workplace Bullying and Harassment: New Developments in International Law provides a comprehensive tour around the globe, summarizing relevant legislation and key developments in workplace bullying, harassment, sexual harassment, discrimination, violence, and stress in over 50 countries in Europe, the Asia Pacific region, the Americas region, and the Middle East and Africa. Workplace bullying, harassment, and other psychological workplace hazards are becoming increasingly acknowledged and legislated against in the modern work world. The costs of bullying, harassment, violence, discrimination, and stress at work are huge and far-reaching. Frequently under-reported and misunderstood, workplace bullying, harassment, violence, discrimination, and stress wreak havoc on the vitality and prosperity of organizations and individuals alike. Workplace laws have long dealt with physical risks, and psychological risks have begun to be treated similarly. In response to the changing workplace, many countries are regulating workplace bullying and harassment by introducing new legislation or incorporating new provisions into existing legislation to address these risks. Other countries have opted for non-regulatory instruments. Numerous European countries, Canada, Australia, and Japan all prohibit and punish workplace bullying and harassment, with other countries, including the United States of America, moving toward legislation against this abusive workplace conduct. This book brings together need-to-know information on global workplace bullying and harassment in one place, the first publication of its kind to do so. It will aid those in the fields of labor and employment, human resources management, occupational and industrial health psychology, health and safety, and workplace regulatory compliance stay abreast of laws and developments that these practitioners must be aware of, whether operating nationally or globally. Academics will also benefit. Links to laws and references are provided, enabling further research."